Pembentukan Individu yang Seimbang dan Holistik: Analisis Filosofi Pendidikan Nasional (NEP) - Mohd Fadzil Jamal1; Muhammad Talhah Ajmain Jima’ain; Mohammad Dzarul Hafiz Dol Malek; Muhammad Dhiauddin Ahmad Termizi; Muaz Muhammad Arif5 (CV Kalimasada Group, 2025)
This study aims to examine the extent to which the concepts of balance and integration are applied within the National Philosophy of Education (FPK) in Malaysia. Essentially, the formulation of FPK reflects the government's aspiration to empower human capital. The government introduced FPK to outline the goals and direction of the national education system. This philosophy has implications for the national education system through an integrated approach that emphasizes the holistic and balanced development of human potential. The elements of integration and balance that FPK seeks to achieve and incorporate are faith, intellect, spirituality, emotions, and physical well-being. The concept of faith, or belief in God, serves as the foundation of FPK. In other words, intellectual, spiritual, emotional, and physical aspects must align with faith and religious teachings. Nowadays, the country faces various social issues, such as baby abandonment, murder, robbery, rape, adultery, corruption, and alcohol consumption. All parties are responsible for addressing these issues, including the education sector. The FPK introduced by the government is expected to help resolve these challenges. This study employs a library research methodology, analyzing several journal articles and other scholarly materials. Hence, the balance and integration envisioned in FPK are hoped to produce students who are knowledgeable, morally upright, faithful, obedient to Allah SWT, physically healthy, and mentally resilient.